Should central banks manage the exchange rate? - Thomas Straubhaar (Intereconomics, 2015)
Should central banks intervene in currency markets? In theory, within a flexible system, central banks should leave the process of determining appropriate exchange rates to the currency markets. In practice, however, central banks have frequently intervened to 'manage' the exchange rates according to their goals and priorities. This article discusses whether central banks can effectively intervene in currency markets and describes some lessons other countries could learn from the Swiss experience.
Keywords: 330; Wechselkurspolitik; Zentralbank; Wechselkurs; Schweizer Franken; Schweiz